Walt Disney's 101 Dalmatians - Braybrooks, Ann.; DiCicco, Gil; Smith, Dodie, 1896-; Walt Disney Productions (New York : Disney Press, 1991)
Pongo the dalmatian and his wife Perdita undertake a daring expedition to rescue their fifteen puppies from the clutches of the vicious Cruella de Vil.
"Based on The one [sic] hundred and one Dalmations by Dodie Smith"--T.p. verso.
Keywords: Dalmatian dog -- Fiction; Dogs -- Fiction; Mystery and detective stories; England -- Fiction